Characterization of podal lesions in dairy cows in the coffee-growing region and northern Valle del Cauca, Colombia - Gómez Parra, Fernando (2023)
The aim of this study was to characterize foot lesions in dairy cows in farms of the coffee-growing region and northern Valle del Cauca. An observational retrospective study was carried out based on bovine podiatric evaluation records. The records of 8671 milk-type cattle from the high and low tropics (n=8548 females, n=123 breeders) located in 28 municipalities of the coffee-growing region and northern Vall del Cauca (n=93 farms) were analyzed. A trained veterinary practitioner with expertise in podiatry performed the evaluation of all the injuries between January 2015 and December 2019. Results showed that 26.07% of the cattle presented some degree of podal injury and of these, 41.45% exhibited alterations in the locomotion. The prevalence of infectious and non-infectious lesions were 7.88% and 92.12%, respectively. Sole hemorrhage was the most frequent pathology (41.4%), followed by sole abscesses (13.8%) and double sole (11.35%). There were significant differences in the prevalence of podal lesions according to month (X2=196.08, p<0.001) and department (X2=13.8, p<0.003). It is concluded that podal lesions and lameness presented a high prevalence, which suggests establishing podiatric evaluation as a routine practice to reduce economic losses to producers and guarantee the welfare of animals.